Factor Affecting the Demand of Food Via Gofood (A Study Case of Millenial and Z Generation Consumers) - Akbar, Dwiky Wahana; Muttaqin, Aminnullah Achmad (Islamic Economics and finance in Focus, 2025)
Online food delivery in Indonesia is growing rapidly. This has influenced consumer behavior to change. The demand of food as a primary need is the reason for the development of online food delivery. The demand of food is dominated by millennials and z generation. The halal factor is the main preference when choosing food. In Islamic perspective, halal food is recommended tobe the main need in order to achieve falah, which means happinesss in this world and the hereafter. This study was conducted with the aim of explaining the effect of religiosity, cleanfood, lifestyle, price, and income toward the demand of food through Gofood. Respondents used in this study were limited to Malang City. This data collection technique was carried out using a questionnaire. The data analysis technique uses Structural Equation Modelling (SEM) with a Confirmatory Factor Aanlysis approach. The result of this study show that cleanfood have a significant impact on food purchasing decision through Gofood. Furthermore, religiosity, lifestyle, price and income have not signifant impact on food purchasing decision through Gofood.